Symptomatology in 1,112 women screened positive and negative using the Edinburgh postnatal depression scale (EPDS): longitudinal observations from the first trimester to 6 weeks postpartum of a Chinese cohort - Lu Liu; Dong (Roman); Yongsheng Tong; Jingcheng Shi; Zhen Zeng; Wenjie Gong (Taylor & Francis Group, 2022)
Purpose To compare the characteristics of depression-related symptoms identified by individual EPDS items in women who screened positive and negative, and to describe the occurrence of thoughts of self-harm in these women. Methods Based on a Chinese cohort of 1,112 women, scores on each EPDS item were analyzed at 7 time points from the first trimester to 6 weeks postpartum. Scores greater than 0 indicated the presence of symptoms, and higher scores indicated more severe symptoms. We defined the most frequent, serious and important symptoms for screening-positive and screening-negative groups as the item with the highest proportion of respondents scoring 1 or higher, highest proportion scoring 3, and highest average score, respectively. Results In screened positive women the most frequent symptom was feeling sad or miserable, and the most serious and important symptoms were both sleeping problems. Among those screened negative, self-blame was the most frequent, serious and important item. For women who screened positive in the first trimester, only self-blame and feeling overwhelmed showed stability over time. Symptoms in women screened negative were relatively stable. Four in ten women who had self-harm thoughts were screened negative. Conclusion Women who screened positive in EPDS differed from those screened negative in the characteristics in depressive symptoms. Intervention strategies focusing on the most frequent, serious and important symptoms (such as sadness and insomnia) may be worthwhile. Health practitioners should be trained to respond to a positive response to thoughts of self-harm, regardless of whether the women are screened positive or negative.